2013
DOI: 10.1172/jci64060
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide sugar UDP-glucose mobilizes long-term repopulating primitive hematopoietic cells

Abstract: Hematopoietic stem progenitor cells (HSPCs) are present in very small numbers in the circulating blood in steady-state conditions. In response to stress or injury, HSPCs are primed to migrate out of their niche to peripheral blood. Mobilized HSPCs are now commonly used as stem cell sources due to faster engraftment and reduced risk of posttransplant infection. In this study, we demonstrated that a nucleotide sugar, UDP-glucose, which is released into extracellular fluids in response to stress, mediates HSPC mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 64 publications
1
37
0
Order By: Relevance
“…Notably, a recent study showed that HSPCs could be mobilized from the BM into the circulation by administration of a prostagrandin E 2 (PGE 2 ) inhibitor, and this effect was independent of CXCL12-CXCR4 signaling [32]. A nucleotide sugar, uridine diphosphate (UDP)-glucose, has also been shown to mobilize subsets of HSPCs functionally distinct from those mobilized by G-CSF, suggesting that UDP-glucose-induced HSPC mobilization would be mediated, at least in part, by different mechanisms from G-CSF [33]. Thus, it would be of interest to examine whether VEGF could influence the levels of BM PGE 2 and/or plasma UDP glucose.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, a recent study showed that HSPCs could be mobilized from the BM into the circulation by administration of a prostagrandin E 2 (PGE 2 ) inhibitor, and this effect was independent of CXCL12-CXCR4 signaling [32]. A nucleotide sugar, uridine diphosphate (UDP)-glucose, has also been shown to mobilize subsets of HSPCs functionally distinct from those mobilized by G-CSF, suggesting that UDP-glucose-induced HSPC mobilization would be mediated, at least in part, by different mechanisms from G-CSF [33]. Thus, it would be of interest to examine whether VEGF could influence the levels of BM PGE 2 and/or plasma UDP glucose.…”
Section: Discussionmentioning
confidence: 99%
“…UDP-glc has been shown to mobilize long-term repopulating HSPCs, and co-administration of UDP-glc and G-CSF led to greater HSPC mobilization than G-CSF alone [143]. In competitive repopulation experiments, HSPCs mobilized with UDP-glc plus G-CSF repopulated better than HSPCs mobilized with G-CSF alone.…”
Section: C1pmentioning
confidence: 97%
“…In competitive repopulation experiments, HSPCs mobilized with UDP-glc plus G-CSF repopulated better than HSPCs mobilized with G-CSF alone. In comparison with G-CSF, UDPglc-mobilized HSPCs exhibited a more lymphoid-biased differentiation capacity, indicating that UDP-glc mobilizes a functionally distinct subset of HSPCs [143]. In contrast, inhibition experiments showed that reactive oxygen species (ROS) are mediators of UDPglc-mediated HSPC mobilization.…”
Section: C1pmentioning
confidence: 99%
See 1 more Smart Citation
“…The natural nucleotide sugar uridine diphosphate glucose (UDP-Glc), normally involved in metabolism and a precursor to glycogen synthesis, was recently shown to selectively mobilize HSC when used alone or in combination with G-CSF [95]. Of note, sorted PB HSC from UDP-Glc-mobilized mice possessed superior long-term engraftment potential compared to phenotypically equivalent HSC harvested from G-CSF-mobilized blood, which is consistent with previous reports indicating G-CSFmobilized HSC have reduced capacity to sustain longterm hematopoiesis [87,96].…”
Section: Carbohydrates: Polysaccharides Synthetic Mimetics and Nuclementioning
confidence: 99%